THE HUMANISTIC PERSPECTIVES AND THE PATRIARCHAL BELIEF IN REBECCA BY DAPHNE DU MAURIER - Novita, Amanda; Syamsudin, Oom Rohmah; Meidasari, Venny Eka (Universitas Indraprasta PGRI, 2024)
This research study aims to investigate and analyze the manifestation of the Humanistic Psychological Perspective and Patriarchal Belief in Daphne Du Maurier's novel,